2015
DOI: 10.1111/sdi.12416
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Binders and Clinical Outcomes in Patients with Stage 5D Chronic Kidney Disease

Abstract: Knowledge informing the prescription and the choice of phosphate binders in end stage kidney disease (ESKD) patients has a weak evidentiary base. To date, no placebo-controlled trial based on meaningful clinical endpoints (death, cardiovascular events, bone fractures) has been performed to test the efficacy of these drugs. By the same token, we still lack solid proof that noncalcium binders afford better clinical outcomes as compared with calcium-based binders. Without proper trials, clinical decisions about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As a consequence, at present, the treatment of hyperphosphatemia is mostly driven by clinical experience and evaluation of the individual patient. 36 Hence, even though numerous drugs are already in use in clinical practice, the "ideal" phosphate binder still does not exist. It should be effective in binding dietary phosphate with low pill burden, minimal gastrointestinal or other untoward effects, and no interaction with other medications; it should be also devoid of safety concerns and inexpensive; 37 this is the reason why new phosphate binders have been approved over recent years and others are being investigated for the treatment of phosphate imbalance in CKD.…”
mentioning
confidence: 99%
“…As a consequence, at present, the treatment of hyperphosphatemia is mostly driven by clinical experience and evaluation of the individual patient. 36 Hence, even though numerous drugs are already in use in clinical practice, the "ideal" phosphate binder still does not exist. It should be effective in binding dietary phosphate with low pill burden, minimal gastrointestinal or other untoward effects, and no interaction with other medications; it should be also devoid of safety concerns and inexpensive; 37 this is the reason why new phosphate binders have been approved over recent years and others are being investigated for the treatment of phosphate imbalance in CKD.…”
mentioning
confidence: 99%
“…It is assumed that reduced phosphate intake will benefit CKD and ESRD patients equally, though Selamet et al [1] found no relationship between 24-hour urine phosphate excretion (a surrogate for oral phosphate intake) and all cause mortality in pre-dialysis patients, suggesting that phosphate intake is not directly linked to serum phosphate levels as it is in dialysis patients. Despite widespread use of oral phosphate binding medications, no clinical trial data support benefit on bone strength, cardiovascular events or death [2]. Observational studies suggest non-calcium binders minimize vascular calcification, but again clinical trial data are lacking.…”
Section: Introductionmentioning
confidence: 99%